A LCP liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad plate and a preparation method thereof

Through the compatibility of the LCP liquid crystal polyester fiber modified with hyperbranched polyester-polyether functional masterbatch and PPO resin, the problem of insufficient peel strength of PCB copper clad plate is solved, and the effect of low dielectric and high peel strength is achieved.

CN115896972BActive Publication Date: 2024-12-20GUANGDONG PULIT MATERIAL TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202211127178.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2024-12-20
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

The compatibility of PPO resin and matrix fabrics in existing PCB copper clad plates is poor, resulting in insufficient peel strength and affecting high-frequency and high-speed applications.

Method used

Modified LCP resin modified with hyperbranched polyester-polyether functional masterbatch is prepared by spinning processing, and a low-dielectric, high-peel strength liquid crystal polyester fabric is formed by plain weaving, and the liquid crystal polyester fabric with low dielectric and high peel strength is formed by micro-adding. Functional masterbatch enhances the compatibility of liquid crystal polyester fibers with polyphenylene ether PPO resin.

Benefits of technology

The peel strength of the PCB copper clad plate is significantly improved, the mechanical properties of the liquid crystal polyester fiber are maintained, the impact of the addition of functional additives on spinning properties is reduced, and excellent performance is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896972B_ABST
    Figure CN115896972B_ABST
Patent Text Reader

Abstract

The present invention discloses a LCP liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate and a preparation method thereof, which mainly comprises 3 to 15 parts of hyperbranched polyester-polyphenylene ether functional masterbatch and 85 to 97 parts of conventional spinning-grade LCP liquid crystal resin. Specifically comprising the following preparation process: (1) a novel polyester-polyphenylene ether copolymer functional masterbatch is prepared by macromolecular structure design; (2) the prepared polyester-polyphenylene ether copolymer functional masterbatch is blended and spun with conventional spinning-grade liquid crystal LCP polyester to form a modified LCP liquid crystal polyester fiber, and then the prepared modified liquid crystal polyester fiber is plain woven into a liquid crystal polyester fabric. The present invention realizes that only a trace amount of the prepared functional masterbatch is added to improve the compatibility of the fully aromatic liquid crystal polyester and the polyphenylene ether resin, and the original mechanical, heat resistance and other properties of the liquid crystal polyester fiber are preserved to the maximum extent through the optimization design of the structure and performance of the material itself.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an LCP liquid crystal polyester fabric for preparing a PCB copper-clad plate with low dielectric and high peel strength and a preparation method thereof, and belongs to the field of fiber material processing and the field of semiconductors. Background Art

[0002] With the miniaturization and high performance of electronic equipment components and the advent of the 5G era, the requirements for copper-clad circuit boards (PCBs) in this field are also developing rapidly towards high density, high precision and high performance. The main indicators used to evaluate the performance of copper-clad PCBs are the two key indicators of dielectric constant Dk and dielectric loss factor Df. The smaller and more stable Dk and Df are, the better the signal transmission performance of high-frequency and high-speed PCB substrates. In addition, higher requirements are also placed on the heat resistance, mechanical properties and flame retardant properties of PCB copper-clad boards.

[0003] Traditional PCB uses glass fiber cloth as a reinforcing material, and its DK is around 6 to 7, which can no longer meet the high-frequency and high-speed requirements of 5G. Fortunately, in recent years, after the exploration and efforts of countless technical practitioners in this field, a series of PCB copper-clad laminate materials that meet the high-frequency and high-speed requirements of the 5G era have been prepared by using a base fabric prepared from LCP liquid crystal polyester materials with high strength, high heat resistance, high frequency and low dielectric, and low dielectric loss and copper foil composites. In addition, PPO resin has been extensively studied by countless industry-related technicians as a curing layer for high-frequency and high-speed PCB copper-clad laminates because of its extremely low and stable dielectric constant and dielectric loss performance. However, due to the poor compatibility of polyphenylene ether PPO resin with glass fiber cloth and LCP liquid crystal polyester fabric, the peel strength of the PCB copper-clad laminate prepared by it is relatively insufficient, and even interlayer delamination damage occurs, which ultimately seriously affects the processing and use quality of the PCB circuit board. Therefore, solving the compatibility problem between PPO resin and base fabric or non-fabricated materials is the main problem affecting its application in the field of high-frequency and high-speed PCB copper-clad laminates.

[0004] For example, patent CN111101256A discloses a liquid crystal polymer fabric and a preparation method, which is characterized in that liquid crystal polymer fibers are prepared by melt spinning, and then the liquid crystal polymer fibers are woven to obtain liquid crystal polymer fabric. The liquid crystal polymer fabric has the characteristics of good strength, uniform thickness, low dielectric constant and dielectric loss factor, and is mainly used for preparing PCB copper clad laminates.

[0005] For example, patent CN202110418357.1 discloses a low-dielectric and high-strength resin composition, which is characterized in that a cross-linking reaction between a functionalized cross-linked polyphenylene ether resin and a thermoplastic resin polymer with a benzene ring structure is used to form a cross-linked network interlaced structure between glass fiber matrix materials, which effectively avoids the problem of phase separation caused by the use of different resin polymers in traditional schemes. However, due to the large amount of high dielectric constant substances such as cross-linking curing agents and thermoplastic resin polymers in the system, the dielectric properties of the PPO resin itself are affected, so that the comprehensive dielectric constant of the finally prepared PCB copper clad laminate is above 3.4. At the same time, due to the presence of the cross-linking reaction, the complexity of the impregnation process of the composition containing the functionalized cross-linked polyphenylene ether resin and the matrix glass fiber cloth is greatly improved, which greatly reduces the production efficiency and increases the preparation cost.

[0006] In order to fundamentally solve the compatibility problem between liquid crystal polymer fabric and PPO resin of copper clad laminate curing layer, the invention team of this case conducted long-term research and exploration on the above-mentioned existing problems, and thus this case was produced. Summary of the invention

[0007] The object of the present invention is to provide an LCP liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate and a preparation method thereof.

[0008] The liquid crystal polyester fabric used for preparing low dielectric and high peel strength PCB copper clad plate is prepared by spinning an LCP resin modified by hyperbranched polyester-polyether functional masterbatch into modified LCP liquid crystal polyester fiber, and then plain weaving the prepared modified liquid crystal polyester fiber.

[0009] The modified LCP resin is prepared by direct blending or single-screw or twin-screw extrusion granulation of the following raw materials in percentage by weight:

[0010] Conventional spinning grade LCP resin: 85-97%;

[0011] Hyperbranched polyester-polyphenylene ether functional masterbatch: 3-15%.

[0012] Wherein, the conventional spinning-grade fully aromatic liquid crystal polyester (LCP) is a polyester resin showing liquid crystal properties in a molten state. The liquid crystal polyester used in the present invention preferably has a melt viscosity of 20 to 100 Pa·S, preferably 30 to 60 Pa·S, and a DSC melting temperature range of 250°C to 350°C, preferably 280 to 335°C. Specifically, it is composed of two or more combinations of aromatic polyacids, aromatic hydroxycarboxylic acids and aromatic polyols as polymerization monomers. The aromatic polyacids and aromatic hydroxycarboxylic acids are aromatic diacids or aromatic hydroxycarboxylic acid compounds such as terephthalic acid, p-hydroxybenzoic acid, 6-hydroxy-2-naphthalenebenzoic acid, 2,6-naphthalene dicarboxylic acid, isophthalic acid, etc., and the aromatic polyol repeating unit is an aromatic diol compound such as 2,6-naphthalene diol, 4.4-dihydroxybiphenyl, hydroquinone, etc.;

[0013] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared by stepwise polymerization reaction of terminal phenolic hydroxyl polyphenylene ether, terephthalic acid PTA, ethylene glycol EG, pyromellitic acid, a catalyst and an anti-aging additive in a reactor under nitrogen protection. The technical scheme is preferentially a functional masterbatch with a phenolic hydroxyl polyphenylene ether monomer content of 20% and a branched pyromellitic acid content of 2%, which is verified by a large number of experiments by the technical team, and has a melt viscosity of 5.0 Pa·S and a melting temperature of 251°C.

[0014] The hyperbranched polyester-polyphenylene ether functional masterbatch is based on the sum of the mass of terephthalic acid and ethylene glycol, and the mass percentages of the remaining components are as follows:

[0015]

[0016] The polymerization equation of the hyperbranched polyester-polyphenylene ether functional masterbatch is as follows:

[0017]

[0018] The terminal hydroxyl polyphenyl ether is a polyphenyl ether with phenolic hydroxyl groups at both ends having a number average molecular weight of 1000 to 50000 as shown in the chemical formula of the above-mentioned MPPO, wherein X1, X2, X3, and X4 can be hydrogen atoms, halogens, alkyl groups and other functional groups but are not limited to the above functional groups, wherein X1, X2, X3, and X4 in this technical solution are preferably H atoms, and R1 and R2 can be alkyl groups, hydrogen atoms, halogens, phenolic hydroxyl groups or alkoxy groups but are not limited to the above functional groups. In this technical solution, preferably R1 and R2 are alkyl methyl groups.

[0019] The catalyst is a titanium catalyst or an antimony catalyst such as titanium glycolate, tetrabutyl titanate or antimony trioxide, antimony glycolate, antimony acetate or a mixture thereof, and antimony glycolate is preferred in the present invention.

[0020] The heat stabilizer is one or a mixture of alkyl phosphate, trimethyl phosphate or phosphite, and the preferred embodiment of the present invention is phosphite.

[0021] The above-mentioned LCP liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate and a preparation method thereof include the following preparation steps:

[0022] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch

[0023] Since the reactivity of different types of diols or other types of polyhydric alcohols with carboxylic acid groups is different, after a large number of polymerization routes and process verifications, it is preferred that after the esterification reaction of terephthalic acid PTA, pyromellitic acid and ethylene glycol EG are completed, they are added into the hydroxyl-terminated polyphenylene ether reactor for transesterification reaction, and after the transesterification reaction is completed, the polycondensation reaction stage is entered, and finally the hyperbranched polyester-polyphenylene ether functional masterbatch is obtained by the polycondensation reaction. The specific preparation technology route is as follows Figure 1 shown.

[0024] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared according to Figure 1 Technical route: In an 80L polyester polymerization reactor, the hyperbranched polyester-polyphenylene ether functional masterbatch is prepared according to the following preparation process. The specific preparation process is as follows:

[0025] Esterification stage: PTA, pyromellitic acid and ethylene glycol EG are weighed according to the acid-alcohol molar ratio of 1:1.3-1.5, and are put into the reactor together with the catalyst and the heat stabilizer to carry out the esterification reaction under nitrogen protection. The reaction conditions are: reaction temperature 230-250°C, pressure 0.25-0.4Mpa, and the temperature at the top of the distillation column is controlled at 110-135°C. The reaction is terminated when the water output reaches 93-95% of the theoretical water output, and the pressure is released to prepare for the ester exchange stage.

[0026] Ester exchange stage: after the pressure of the reactor is released to normal pressure, the pre-weighed hydroxyl-terminated polyphenylene ether is put into the reactor, the pressure of the reactor is adjusted by filling with nitrogen, and the ester exchange reaction begins. The reaction temperature is 230-250°C, the pressure in the reactor is 0.25-0.4Mpa, and the temperature at the top of the fractionation column is 110-135°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to prepare for the polycondensation stage.

[0027] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 20-60Pa, and after the discharge power reaches the predetermined value (the stirring power setting value of the 80L reactor is 200W-250W), the polycondensation reaction ends, and the vacuum discharge is removed and granulated to prepare branched polyester-polyphenylene ether functional masterbatch.

[0028] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method has the characteristics of high fluidity and low intrinsic viscosity due to its special spherical branched macromolecular structure. The melt viscosity of the prepared functional masterbatch is 3-20 Pa·S and the melting temperature is 210°C-260°C.

[0029] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:

[0030] iii. Preparation of modified all-aromatic liquid crystal LCP polyester chips

[0031] The modified fully aromatic liquid crystal LCP polyester is prepared by direct physical blending or single-screw or twin-screw extrusion granulation of the branched polyester-polyphenylene ether functional masterbatch prepared above and conventional spinning-grade LCP liquid crystal polyester in proportions by weight:

[0032] Conventional spinning grade LCP resin: 85-97%

[0033] Hyperbranched polyester-polyphenylene ether functional masterbatch: 3-15%

[0034] The single-screw and double-screw extrusion process of the modified fully aromatic liquid crystal LCP polyester is as follows: the extrusion temperature is 290°C to 360°C, the main screw speed is 500 to 550 r / min, and the water tank temperature is 30°C to 60°C.

[0035] iv. Preparation of modified fully aromatic LCP fibers:

[0036] The functional masterbatch prepared above is directly blended with the modified wholly aromatic liquid crystal polyester or extruded slices are melt-spun through a single / twin screw spinning machine. The technical solution is preferably to physically blend the prepared functional masterbatch with the spinning-grade LCP liquid crystal polyester resin after vacuum drying to prepare the modified liquid crystal LCP fiber. The specific process parameters are as follows:

[0037] The drying temperature of polyester-polyphenylene ether masterbatch is 80℃~110℃, the vacuum degree is 10~30Pa, and the drying time is 12~24 hours; the drying temperature of modified aromatic LCP resin chips and conventional spinning-grade LCP polyester chips is 100℃~130℃, the vacuum degree is 10~30Pa, and the drying time is 8~12 hours.

[0038] Spinning process: spinning machine screw temperature 260 ~ 360 ℃, spinning die temperature 260 ~ 360 ℃, drafting roller temperature 70 ~ 120 ℃, spinning tunnel temperature 150 ~ 250 ℃, metering pump frequency 10 ~ 50HZ, spinning speed 500m / min ~ 2000m / min, drafting multiple 1.0 ~ 1.5 times.

[0039] (3) Preparation of liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminates:

[0040] The modified liquid crystal polymer fiber prepared above is woven to obtain a liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate, wherein the warp density is between 3 and 35 / cm, and the weft density is between 3 and 35 / cm. The thickness of the woven liquid crystal polymer fabric is between 15 and 250 microns and the tolerance is within 20%.

[0041] The present invention provides an LCP liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad plates and a preparation method thereof. The method mainly comprises spinning an LCP resin modified by a hyperbranched polyester-polyether functional masterbatch into a modified LCP liquid crystal polyester fiber, and then plain weaving the prepared modified liquid crystal polyester fiber.

[0042] The hyperbranched polyester-polyphenylene ether functional masterbatch is a novel polyester-polyphenylene ether copolymer prepared by investing a lot of effort in the exploration of polymerization routes and processes from the perspective of macromolecular structure design. The polyester segment in the branched polyester-polyphenylene ether molecular structure gives the copolymer compatibility with aromatic polyesters, while the polyphenylene ether segment gives the copolymer compatibility with polyphenylene ether PPO resins. In addition, the special spherical branched macromolecular structure of the masterbatch itself gives the functional masterbatch ultra-high flow properties and low melt viscosity properties. When the blended slices or modified slices containing the hyperbranched polyester-polyphenylene ether functional masterbatch and conventional spinning-grade wholly aromatic polyester are subjected to twin-screw extrusion or single-screw blending spinning, due to the low melt viscosity and high fluidity of the functional masterbatch itself, it will first quickly distribute to both sides of the melt at the spinneret position, thereby achieving the branched polyester-polyphenylene ether functional masterbatch resin preferentially enriched on the surface of the wholly aromatic liquid crystal polyester fiber, effectively improving the compatibility of the liquid crystal polyester fabric prepared from the modified liquid crystal polyester fiber and the polyphenylene ether PPO resin, and playing a role in improving the problem of insufficient peel strength of the PCB copper clad plate prepared therefrom.

[0043] Compared with the prior art, the technical solution of the present invention has the following technical advantages:

[0044] (1) An LCP liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad laminate and a preparation method thereof. The present invention combines the industry pain points of the current application of liquid crystal LCP polyester fabrics in the field of low dielectric PCB copper clad laminates, prepares a new polyester-polyphenylene ether copolymer, also known as a hyperbranched polyester-polyphenylene ether functional masterbatch from the perspective of macromolecular structure, and combines the polymer modification technology with the prepared functional masterbatch to modify the conventional spinning-grade liquid crystal LCP polyester. By optimizing the structure and performance of the material itself, only a small amount of the prepared functional masterbatch is needed to improve the compatibility of the wholly aromatic liquid crystal polyester and the polyphenylene ether resin, thereby improving the problem of insufficient peel strength of the PCB copper clad laminate prepared therefrom.

[0045] (2) In view of the excellent properties of the prepared hyperbranched polyester-polyether functional masterbatch itself, the branched polyester-polyphenylene ether functional masterbatch resin is ultimately enriched on the surface of the wholly aromatic liquid crystal polyester fiber, while the interior of the fiber contains no or only a small amount of functional resin. Only a small amount of addition is needed to greatly improve the compatibility of the wholly aromatic liquid crystal polyester fiber and the polyphenylene ether resin, thereby preserving the original mechanics of the liquid crystal polyester fiber to the greatest extent and reducing the effect of the addition of functional additives on the spinnability of the liquid crystal polyester, thereby ultimately ensuring the excellent performance of the liquid crystal resin fabric prepared therefrom. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a technical roadmap for the synthesis of hyperbranched polyester-polyphenylene ether copolymer masterbatch. DETAILED DESCRIPTION

[0047] Below in conjunction with specific embodiment, further elaborate content of the present invention.It should be emphasized that these embodiments are only used for further explanation of the present invention, and can not be interpreted as limiting the scope of protection of the present invention.In addition, it should be understood that after reading the content described in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0048] The spinning-grade wholly aromatic polyester resins in the following examples are selected from spinning-grade LCP resins prepared by Shanghai Pulite Chemical Co., Ltd. with melting points of 280°C, 310°C, 335°C, and melt viscosities of 35 Pa·S, 40 Pa·S, and 50 Pa·S, respectively.

[0049] The branched polyester-polyphenylene ether functional masterbatch is a functional masterbatch with a phenolic hydroxyl polyphenylene ether monomer content of 20% and a branched pyromellitic acid content of 2%, which is verified by a large number of experiments by the technical team. The melt viscosity is 5.0 Pa·S and the melting temperature is 251°C. It is specifically prepared from the following raw materials in parts by weight:

[0050]

[0051] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.

[0052] The catalyst is antimony glycol.

[0053] The heat stabilizer is phosphite.

[0054] The above-mentioned fully aromatic liquid crystal polyester fiber which is conducive to PPO resin compounding and its preparation method include the following preparation steps:

[0055] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch

[0056] Esterification stage: PTA, 15 kg of ethylene glycol EG, 0.30 kg of pyromellitic acid, 3 g of catalyst ethylene glycol antimony, and 45 g of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3 MPa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.

[0057] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 3.0 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.

[0058] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether copolymer functional masterbatch.

[0059] In the embodiment, the functional masterbatch provided by the technical team and the spinning-grade LCP liquid crystal polyester resin are directly physically blended and spun after vacuum drying to prepare the modified liquid crystal LCP fiber.

[0060] Example 1

[0061] An LCP liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate and a preparation method thereof, comprising: blending and spinning LCP with a melt viscosity of 35 Pa·S, 40 Pa·S, 50 Pa·S and a DSC melting temperature of 280°C with a prepared branched polyester-polyphenylene ether functional masterbatch according to a weight ratio of 97:3, 95:5, 90:10, 85:15 to form a modified LCP liquid crystal polyester fiber, and then plain weaving the prepared modified liquid crystal polyester fiber. The preparation mainly comprises the following steps:

[0062] (1) Preparation of modified fully aromatic liquid crystal LCP polyester fiber:

[0063] The branched polyester-polyphenylene ether functional masterbatch prepared above and the fully aromatic LCP resin with a spinning grade melt viscosity of 35 Pa·S, 40 Pa·S, 50 Pa·S and a DSC melting temperature of 280°C were mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended spinning slice, and then the blended spinning slice was melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:

[0064] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.

[0065] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270°C, 285°C, 290°C, 300°C, 305°C, 305°C respectively, the spinning die head is set to 305°C, the drafting roller is set to 85°C, the spinning tunnel is set to 170°C, the metering pump is set to 22HZ, the spinning speed is set to 1500m / min and the drafting multiple is 1.25 times.

[0066] The spinnability of the above-mentioned different spinning speeds and different proportions of resins was evaluated, and the tensile strength of the fully aromatic liquid crystal polyester fibers prepared therefrom was tested. The fabric woven therefrom was used to prepare a PCB copper-clad board and its peel strength and dielectric constant were tested.

[0067] (2) Preparation of liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminates:

[0068] The modified liquid crystal polymer fiber prepared above is woven to obtain a liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate, wherein the warp density is between 15 / cm and the weft density is 15 / cm.

[0069] The spinnability of the branched polyester-polyphenylene ether functional masterbatch was evaluated in different proportions with fully aromatic LCP resins of different viscosities, and the tensile strength of the prepared modified fully aromatic liquid crystal polyester fiber was tested. The fabric woven therefrom was used to prepare a PCB copper clad laminate and its peel strength and dielectric constant were tested.

[0070] Example 2

[0071] An LCP liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate and a preparation method thereof, comprising: blending and spinning LCP with a melt viscosity of 35 Pa·S, 40 Pa·S, 50 Pa·S and a DSC melting temperature of 310°C with a prepared branched polyester-polyphenylene ether functional masterbatch according to a weight ratio of 97:3, 95:5, 90:10, 85:15 to form a modified LCP liquid crystal polyester fiber, and then plain weaving the prepared modified liquid crystal polyester fiber. The preparation mainly comprises the following steps:

[0072] (1) Preparation of modified fully aromatic liquid crystal LCP polyester fiber:

[0073] The branched polyester-polyphenylene ether functional masterbatch prepared above and the fully aromatic LCP resin with a spinning grade melt viscosity of 35 Pa·S, 40 Pa·S, 50 Pa·S and a DSC melting temperature of 310°C were mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended spinning slice, and then the blended spinning slice was melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:

[0074] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.

[0075] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 310℃, 315℃, 315℃, 320℃, 320℃, 325℃ respectively, the spinning die head is set to 325℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speed is set to 1500m / min and the drafting multiple is 1.25 times.

[0076] (2) Preparation of liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminates:

[0077] The modified liquid crystal polymer fiber prepared above is woven to obtain a liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate, wherein the warp density is between 15 / cm and the weft density is 15 / cm.

[0078] The spinnability of the branched polyester-polyphenylene ether functional masterbatch was evaluated in different proportions with fully aromatic LCP resins of different melt viscosities, and the tensile strength of the modified fully aromatic liquid crystal polyester fiber prepared therefrom was tested. The fabric woven therefrom was used to prepare a PCB copper-clad laminate and its peel strength and dielectric constant were tested.

[0079] Example 3

[0080] An LCP liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate and a preparation method thereof, comprising: a spinning-grade LCP resin having a melt viscosity of 35 Pa·S, 40 Pa·S, 50 Pa·S and a DSC melting temperature of 335°C and a prepared branched polyester-polyphenylene ether functional masterbatch are blended and spun into a modified LCP liquid crystal polyester fiber according to a weight ratio of 97:3, 95:5, 90:10, 85:15, and then plain weaving the prepared modified liquid crystal polyester fiber. The preparation method mainly comprises the following preparation steps:

[0081] (1) Preparation of modified fully aromatic liquid crystal LCP polyester fiber:

[0082] The branched polyester-polyphenylene ether functional masterbatch prepared above and the fully aromatic LCP resin with a spinning grade melt viscosity of 35 Pa·S, 40 Pa·S, 50 Pa·S and a DSC melting temperature of 335°C were mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended spinning slice, and then the blended spinning slice was melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:

[0083] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.

[0084] Blended chip spinning process: The processing temperatures of zones 1 to 5 of the spinning machine screw are set to 330°C, 335°C, 335°C, 340°C, 340°C, and 345°C respectively, the spinning die head is set to 345°C, the drafting roller is set to 85°C, the spinning tunnel is set to 170°C, the metering pump is set to 22HZ, the spinning speed is set to 1500m / min and the drafting multiple is 1.25 times.

[0085] (2) Preparation of liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminates:

[0086] The modified liquid crystal polymer fiber prepared above is woven to obtain a liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate, wherein the warp density is between 15 / cm and the weft density is 15 / cm.

[0087] The spinnability of the branched polyester-polyphenylene ether functional masterbatch was evaluated in different proportions with fully aromatic LCP polyesters of different melt viscosities, and the tensile strength of the modified fully aromatic liquid crystal polyester fibers prepared therefrom was tested. The fabric woven therefrom was used to prepare a PCB copper-clad laminate and its peel strength and dielectric constant were tested.

[0088] Comparative Example 1

[0089] Spinning-grade fully aromatic liquid crystal LCP resins with melt viscosities of 35 Pa·S, 40 Pa·S, 50 Pa·S and DSC melting temperatures of 280°C, 310°C, and 335°C are directly used to spin into conventional LCP liquid crystal polyester fibers according to the following spinning process.

[0090] The modified liquid crystal polymer fiber prepared above is woven to obtain a liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate, wherein the warp density is between 15 / cm and the weft density is 15 / cm.

[0091] The spinnability of the conventional spinning-grade LCP liquid crystal polyester was evaluated, and the tensile strength of the conventional wholly aromatic liquid crystal polyester fiber prepared therefrom, as well as the peel strength and dielectric constant of the PCB copper clad board prepared from the fabric woven therefrom were tested.

[0092] Comparative Example 2

[0093] The PPO masterbatch prepared by direct physical blending of PPO resin and spinning-grade fully aromatic liquid crystal LCP resin with melt viscosity of 35Pa·S, 40Pa·S, 50Pa·S and DSC melting temperature of 280℃, 310℃, 335℃ was blended and spun with fully aromatic liquid crystal polyester to form modified LCP liquid crystal polyester fiber, and then the prepared modified liquid crystal polyester fiber was plain woven into liquid crystal polyester fabric, and the relevant properties were tested and evaluated. The specific operation steps are as follows:

[0094] The invention is prepared by blending and spinning spinning-grade fully aromatic liquid crystal LCP and prepared PPO resin masterbatch in a weight ratio of 97:3, 95:5, 90:10 and 85:15.

[0095] The PPO resin masterbatch is prepared from the following raw materials in parts by weight:

[0096] Spinning grade LCP resin: 80%

[0097] PPO resin: 20%

[0098] The PPO resin is a PPO resin used for the curing layer of conventional high-frequency and high-speed PCB copper-clad laminates.

[0099] The above-mentioned PPO resin composite fully aromatic liquid crystal polyester fiber and its preparation method include the following preparation steps:

[0100] (1) Preparation of PPO resin masterbatch

[0101] According to weight proportions, spinning-grade fully aromatic liquid crystal LCP resin and PPO resin with melt viscosities of 35 Pa·S, 40 Pa·S, and 50 Pa·S and DSC melting temperatures of 280°C and 310°C are uniformly mixed in a premix and then extruded and granulated using a twin-screw extruder. The screw extrusion temperature is set to the melting point temperature + 15°C, the main screw speed is 500-550r / min, and the water tank temperature is 30°C-60°C.

[0102] (2) Preparation of PPO directly modified fully aromatic liquid crystal polyester fabrics:

[0103] The polyphenylene ether PPO masterbatch and the spinning-grade fully aromatic LCP resin are vacuum dried and mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 to obtain a blended spinning slice, and then the blended spinning slice is melt-spun through a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding. The modified liquid crystal polymer fiber prepared above is woven to obtain a liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper-clad board, wherein the warp density is between 15 / cm and the weft density is 15 / cm.

[0104] The spinnability of the polyphenylene ether PPO masterbatch was evaluated in different proportions with fully aromatic LCP resins of different viscosities, and the tensile strength of the prepared modified fully aromatic liquid crystal polyester fiber, as well as the peel strength and dielectric constant of the PCB copper clad board prepared from the fabric woven therefrom were tested.

[0105] A series of modified wholly aromatic liquid crystal polyester fibers and fabrics woven therefrom prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 2 were prepared into PCB copper clad boards, and performance tests were carried out according to the following test standards and conditions. The test data are shown in Tables 1 and 2.

[0106] The fiber strength test was conducted according to the method described in JIS L1013:2010. The strength of the prepared LCP fiber monofilament was tested at a tensile speed of 50 mm / min. Each fiber was tested 30 times, and the arithmetic mean of the test results was taken.

[0107] The PCB peel strength test is carried out according to the IPC-TM-650 2.4.9 test method, and the recorded data is the smaller peel strength value between the two sides of the double-sided board.

[0108] The dielectric constant test was performed using an Agilent N5230A instrument with an SPDR fixture at a measurement frequency of 10 GHz.

[0109] The spinnability is evaluated mainly by evaluating the spinnability of LCP liquid crystal polyester resins with different viscosities and melting points at different masterbatch addition amounts at a spinning rate of 1500m / min. If there is no broken or filamentous yarn in the spinning process and the spinning continuity is good, the spinnability is evaluated as good; if there are intermittent broken or filamentous yarns in the spinning process, but the spinning continuity is acceptable, the spinnability is evaluated as good; if there are broken or filamentous yarns very easily in the spinning process and the spinning continuity is poor, the spinnability is evaluated as poor.

[0110] Table 1 Mechanical properties and spinnability evaluation of LCP liquid crystal polyester fibers in Examples 1-2 and Comparative Examples 1-2

[0111]

[0112]

[0113] Note: The above-mentioned fiber tensile strength shows no data, which means that the spinning was not successful and there is no product data.

[0114] Table 2 Performance evaluation of PCB copper clad laminates prepared from fully aromatic liquid crystal LCP polyester fabrics in Examples 1 to 3 and Comparative Examples 1 to 2

[0115]

[0116] Table 1 is an evaluation of the mechanical properties and spinnability of LCP liquid crystal polyester fibers of Examples 1 to 3 and Comparative Examples 1 to 2. From the analysis of the test data results, it is found that compared with Comparative Example 2, the present technical solution greatly improves the spinnability of the modified LCP liquid crystal resin and the mechanical properties of the modified fiber prepared therefrom. Compared with the conventional spinning-grade liquid crystal LCP polyester of Comparative Example 1, the spinnability of the modified LCP liquid crystal polyester prepared by the present technical solution and the mechanical properties of the modified fiber are slightly reduced but not much, and can still meet the spinning requirements of LCP liquid crystal polyester and the weaving requirements of its fibers.

[0117] Table 2 is a performance evaluation of PCB copper clad laminates prepared from wholly aromatic LCP liquid crystal polyester fabrics according to Examples 1 to 3 and Comparative Examples 1 to 2. From the analysis of the test data, it is found that compared with Comparative Examples 1 to 2, the modified LCP liquid crystal polyester fabric prepared by the present technical solution can greatly improve the peel strength of the PCB copper clad laminates prepared therefrom, and the dielectric strength of the prepared PCB copper clad laminates is within 3.2, and has low dielectric properties.

Claims

1. A liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminate, characterized in that: An LCP resin modified by a hyperbranched polyester-polyether functional masterbatch is processed into a modified LCP liquid crystal polyester fiber by spinning, and then the prepared modified liquid crystal polyester fiber is plain woven; The modified LCP resin is prepared by direct blending or single-screw or twin-screw extrusion granulation of the following raw materials in percentage by weight: Conventional spinning grade LCP resin: 85 ~ 97%; Hyperbranched polyester-polyphenylene ether functional masterbatch: 3 ~ 15%; The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared by stepwise polymerization reaction of terminal phenolic hydroxyl polyphenylene ether, terephthalic acid PTA, ethylene glycol EG, pyromellitic acid, a catalyst and a heat stabilizer in a reactor under nitrogen protection; The hyperbranched polyester-polyphenylene ether functional masterbatch is based on the sum of the mass of terephthalic acid and ethylene glycol, and each component is prepared according to the following dosage: 10 ~ 30% of polyphenylene ether with terminal phenolic hydroxyl groups; Pyromellitic acid 1 ~ 3%; Catalyst 100 ~ 500ppm; Heat stabilizer 0.1 ~ 0.5%; Terephthalic acid and ethylene glycol remaining components; The conventional spinning-grade LCP resin is a polyester resin showing liquid crystal properties in a molten state, the melt viscosity of the liquid crystal polyester is 20-100 Pa·S, and the DSC melting temperature range is 250°C-350°C; it is specifically prepared from one or more of aromatic polyacids, aromatic hydroxycarboxylic acids and aromatic polyols as polymerization monomers; the catalyst is one or a mixture of titanium-based catalysts or antimony-based catalysts.

2. The liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad laminate according to claim 1, characterized in that: The melt viscosity of the liquid crystal polyester is 30-60 Pa·S, and the DSC melting temperature ranges from 280-335°C.

3. The liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad laminate according to claim 1, characterized in that: The aromatic polyacid and aromatic hydroxycarboxylic acid are selected from terephthalic acid, p-hydroxybenzoic acid, 6-hydroxy-2-naphthalenebenzoic acid, 2,6-naphthalene dicarboxylic acid, and isophthalic acid; the aromatic polyol is 2,6-naphthalene diol, 4,4-dihydroxybiphenyl, and hydroquinone.

4. The liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad laminate according to claim 1, characterized in that: The hyperbranched polyester-polyphenylene ether functional masterbatch is a functional masterbatch with a terminal phenol hydroxyl polyphenylene ether monomer content of 20% and a pyromellitic acid content of 2%, a melt viscosity of 5.0 Pa·S, and a melting temperature of 251°C.

5. The liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminate according to claim 1, characterized in that: The polymerization equation of the hyperbranched polyester-polyphenylene ether functional masterbatch is as follows: 。 6. The liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad laminate according to claim 5, characterized in that: The hydroxy-terminated polyphenylene ether shown in the MPPO chemical formula is a polyphenylene ether with a number average molecular weight of 1000 to 50000 and phenolic hydroxyl groups at both ends, wherein X1, X2, X3, and X4 are selected from hydrogen atoms, halogens, and alkyl functional groups; and R1 and R2 are selected from alkyl groups, hydrogen atoms, halogens, phenolic hydroxyl groups, and alkoxy functional groups.

7. The liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminate according to claim 6, characterized in that: The X1, X2, X3, and X4 are H atoms; and R1 and R2 are alkylmethyl groups.

8. The liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad laminate according to claim 1, characterized in that: The catalyst is one or a mixture of titanium glycolate, tetrabutyl titanate, antimony trioxide, antimony glycolate and antimony acetate.

9. The liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminate according to claim 8, characterized in that: The catalyst is antimony glycol.

10. The liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminate according to claim 1, characterized in that: The heat stabilizer is one or a mixture of alkyl phosphate, trimethyl phosphate or phosphite.

11. The liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminate according to claim 10, characterized in that: The heat stabilizer is phosphite.

12. A method for preparing LCP liquid crystal polyester fabric for preparing low dielectric and high peel strength PCB copper clad laminate according to any one of claims 1 to 11, characterized in that: The method comprises the following preparation steps: (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch After the esterification reaction of terephthalic acid PTA, pyromellitic acid and ethylene glycol EG is completed, they are added into the hydroxy-terminated polyphenylene ether reactor for transesterification reaction. After the transesterification reaction is completed, the polycondensation reaction stage is entered, and finally the hyperbranched polyester-polyphenylene ether functional masterbatch is obtained through the polycondensation reaction. The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared in an 80L polyester polymerization reactor according to the following preparation process. The specific preparation process is as follows: Esterification stage: PTA, pyromellitic acid and ethylene glycol EG are weighed according to the acid-alcohol molar ratio of 1:1.3-1.5, and are put into the reactor together with the catalyst and the heat stabilizer to carry out the esterification reaction under the protection of nitrogen. The reaction conditions are: reaction temperature 230-250℃, pressure 0.25-0.4Mpa, and the temperature at the top of the fractionation column is controlled at 110-135℃. The reaction ends when the water output reaches 93-95% of the theoretical water output, and the pressure is released to prepare for the ester exchange stage; Transesterification stage: after the pressure of the reactor is released to normal pressure, the pre-weighed hydroxyl-terminated polyphenylene ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the transesterification reaction begins. The reaction temperature is 230-250°C, the pressure in the reactor is 0.25-0.4Mpa, and the temperature at the top of the fractionation column is 110-135°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to prepare for the polycondensation stage. Polycondensation stage: after the pressure of the reactor drops to normal pressure, vacuumization is started for polycondensation reaction, the vacuum degree is 20~60Pa, and after the discharge power reaches the predetermined value of 200W~250W of the stirring power setting value of the 80L reactor, the polycondensation reaction is completed, and the vacuum discharge is removed and granulated to prepare hyperbranched polyester-polyphenylene ether functional masterbatch; The prepared functional masterbatch has a melt viscosity of 3~20Pa·S and a melting temperature of 210℃~260℃; (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber: ⅰ. Preparation of modified all-aromatic liquid crystal LCP polyester chips The modified fully aromatic liquid crystal LCP polyester is prepared by direct physical blending or single-screw or twin-screw extrusion granulation of the hyperbranched polyester-polyphenylene ether functional masterbatch prepared above and conventional spinning-grade LCP liquid crystal polyester in proportions by weight: Conventional spinning grade LCP resin: 85 ~ 97%; Hyperbranched polyester-polyphenylene ether functional masterbatch: 3 ~ 15%; The single-screw and double-screw extrusion process of the modified fully aromatic liquid crystal LCP polyester is as follows: the extrusion temperature is 290°C to 360°C, the main screw speed is 500 to 550 r / min, and the water tank temperature is 30°C to 60°C; ⅱ. Preparation of modified fully aromatic LCP fibers: The prepared functional masterbatch and spinning-grade LCP liquid crystal polyester resin are directly physically blended and spun after vacuum drying to prepare modified liquid crystal LCP fibers. The specific process parameters are as follows: The drying temperature of polyester-polyphenylene ether masterbatch is 80℃~110℃, the vacuum degree is 10~30Pa, and the drying time is 12~24 hours; the drying temperature of modified fully aromatic LCP resin chips and conventional spinning-grade LCP polyester chips is 100℃~130℃, the vacuum degree is 10~30Pa, and the drying time is 8~12 hours; Spinning process: spinning machine screw temperature 260 ~ 360 ℃, spinning die temperature 260 ~ 360 ℃, drafting roller temperature 70 ~ 120 ℃, spinning tunnel temperature 150 ~ 250 ℃, metering pump frequency 10 ~ 50HZ, spinning speed 500m / min ~ 2000m / min, drafting multiple 1.0 ~ 1.5 times; (3) Preparation of liquid crystal polyester fabric for low dielectric and high peel strength PCB copper clad laminate: The modified fully aromatic LCP fiber prepared as above is woven to obtain a liquid crystal polyester fabric for preparing a low dielectric and high peel strength PCB copper clad plate, wherein the warp density is between 3 and 35 / cm and the weft density is between 3 and 35 / cm; the thickness of the woven liquid crystal polymer fabric is between 15 and 250 microns and the tolerance is within 20%.

Citation Information

Cited By

  • Preparation method and application for enhancing spinning capability of LCP (Liquid Crystal Polymer)

    CN121471668A